METODE DISKUSI DALAM PUSARAN PENDIDIKAN AGAMA KRISTEN PADA ERA DIGITAL - Aser Lasfeto; Anastasia Runesi; Jeany Nanan Wafumilena; Yosua; Rusniati Manik (Bethel Press, 2021)
The digital era demands a transformation in teaching methodologies to align with the needs of modern education. The discussion method, deeply rooted in a rich educational tradition from the times of Socrates to the contemporary era, remains relevant due to its effectiveness in shaping students' critical thinking and communication skills. This study explores the implementation of the discussion method in the context of digital learning, focusing on the use of technologies such as Google Classroom, which facilitates student dialogue and collaboration without spatial and temporal boundaries. Through a qualitative approach and literature review, this study identifies that the discussion method not only enhances student engagement but also supports collaborative learning and a deep understanding of the material. Teachers, in their role as facilitators, are at the forefront of designing and leading discussions that enable students to express their views effectively, listen empathetically, and collaborate in problem-solving. Despite facing challenges such as uneven student participation and the need for high-level facilitation skills from teachers, the discussion method remains a vital tool in the pedagogical toolkit for 21st-century education. This research confirms that with appropriate technological support and effective strategies, discussions can greatly enrich students' learning experiences, preparing them not only academically but also as critical thinkers and responsible citizens.